Efektifitas Terapi Emotional FreedomTechnique (EFT) TerhadapTingkat Stres Mahasiswa Keperawatan Tingkat Akhir Di Universitas Indonesia Maju - Lisna Faunziah; Susaldi Susaldi; Irawan Danismaya (Universitas Katolik Widya Karya Malang, 2023)
Background : Stress is an event that often occurs can be caused by external factors such as task demands, and internal factors such as behavior. Objective: to determine the effectiveness of Emotional Freedom Technique (EFT) therapy on the stress level of final year nursing students at the University of Indonesia Maju. Methods: This type of research is quantitative with a quasy experimental one group pretest-posttest design. The sampling technique used is non-random sampling. The instruments used are observation sheets and the DASS questionnaire (Depression Anxiety Stress Scales-42). Statistical tests use the Wilcoxon test. . Results: the study showed a p-value of 0.000 <0.005, which means that there is effectiveness of Emotional Freedom Technique (EFT) therapy on stress levels.